2018
DOI: 10.1073/pnas.1806996115
|View full text |Cite
|
Sign up to set email alerts
|

Preordering of water is not needed for ice recognition by hyperactive antifreeze proteins

Abstract: Antifreeze proteins (AFPs) inhibit ice growth in organisms living in cold environments. Hyperactive insect AFPs are particularly effective, binding ice through "anchored clathrate" motifs. It has been hypothesized that the binding of hyperactive AFPs to ice is facilitated by preordering of water at the ice-binding site (IBS) of the protein in solution. The antifreeze protein AFP displays the best matching of its binding site to ice, making it the optimal candidate to develop ice-like order in solution. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 59 publications
4
122
0
Order By: Relevance
“…Figure B shows a simulation of spruce budworm AFP and its hypothesized binding to the prism plane via coordinated water molecules providing a match . Whilst the molecular binding details are still under investigation, there is overwhelming evidence for AFPs binding to ice faces and strong evidence of molecular level interactions have been determined . However, for the facially amphipathic molecules, with no evidence for ice binding, an alternative molecular level mechanism which can give rise to IRI is required.…”
Section: Facially Amphiphilic Non‐ice‐binding Materials and Compoundsmentioning
confidence: 99%
“…Figure B shows a simulation of spruce budworm AFP and its hypothesized binding to the prism plane via coordinated water molecules providing a match . Whilst the molecular binding details are still under investigation, there is overwhelming evidence for AFPs binding to ice faces and strong evidence of molecular level interactions have been determined . However, for the facially amphipathic molecules, with no evidence for ice binding, an alternative molecular level mechanism which can give rise to IRI is required.…”
Section: Facially Amphiphilic Non‐ice‐binding Materials and Compoundsmentioning
confidence: 99%
“…This layer can then be easily incorporated into the growing ice crystal, binding the protein to the solid-liquid interface (12). Recent work by Hudait et al (13) has shown that water near the IBS is not truly ice like, since its structural order is much lower than ice, but simulations do show that water near the IBS displays exceptionally slower hydrogen bond reorientation dynamics compared with other protein surfaces (14). The presence of slow hydrogen bond dynamics near the IBS was also confirmed experimentally by Meister et al (15).…”
Section: ∆T = αPmentioning
confidence: 99%
“…Water freezing on various material surfaces is of importance in wide-ranging fields [1][2][3][4][5] such as cloud seeding in climate, frost heaving, and cell preserving. So far, the microscopic mechanisms of the key process of freezing on substrates, the heterogeneous ice nucleation, still remains elusive [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%